Polymorphisms of homologous recombination genes and clinical outcomes of non-small cell lung cancer patients treated with definitive radiotherapy. - Ming Yin; Zhongxing Liao; Yu-Jing Huang; Zhensheng Liu; Xianglin Yuan; Daniel Gomez; Li-E Wang; Qingyi Wei (PLoS ONE, 2011)
The repair of DNA double-strand breaks (DSBs) is the major mechanism to maintain genomic stability in response to irradiation. We hypothesized that genetic polymorphisms in DSB repair genes may affect clinical outcomes among non-small cell lung cancer (NSCLC) patients treated with definitive radio(chemo)therapy. We genotyped six potentially functional single nucleotide polymorphisms (SNPs) (i.e., RAD51 -135G>C/rs1801320 and -172G>T/rs1801321, XRCC2 4234G>C/rs3218384 and R188H/rs3218536 G>A, XRCC3 T241M/rs861539 and NBN E185Q/rs1805794) and estimated their associations with overall survival (OS) and radiation pneumonitis (RP) in 228 NSCLC patients. We found a predictive role of RAD51 -135G>C SNP in RP development (adjusted hazard ratio [HR] = 0.52, 95% confidence interval [CI], 0.31-0.86, P = 0.010 for CG/CC vs. GG). We also found that RAD51 -135G>C and XRCC2 R188H SNPs were independent prognostic factors for overall survival (adjusted HR = 1.70, 95% CI, 1.14-2.62, P = 0.009 for CG/CC vs. GG; and adjusted HR = 1.70; 95% CI, 1.02-2.85, P = 0.043 for AG vs. GG, respectively) and that the SNP-survival association was most pronounced in the presence of RP. Our study suggests that HR genetic polymorphisms, particularly RAD51 -135G>C, may influence overall survival and radiation pneumonitis in NSCLC patients treated with definitive radio(chemo)therapy. Large studies are needed to confirm our findings.